Parking demand analysis among students during car free day using level of services and geographic information system - Nicky Laila Abdullah, 1995-, author 625500; Shahabuddin Amerudin supervisor 450153; Fakulti Alam Bina dan Ukur 619090 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Project Paper (Sarjana Muda Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2019